Medical Assistance in Dying: Challenges for Psychiatry - Jones, Roland M.; Simpson, Alexander I. F. (Frontiers in Psychiatry, 2018)
Medical Assistance in Dying (MAiD), which comprises euthanasia and medically assisted suicide, is practiced in a growing number of countries and jurisdictions. In countries where it is permitted, the individual who requests it must be experiencing severe pain and suffering, but not all countries require the individual to be terminally ill. In some countries the suffering may be caused by a mental disorder in the absence of physical illness or disease. The consideration of mental illness as the sole indication for MAiD is likely to be considered in more jurisdictions. However, the ethical duties of a doctor to promote health, reduce suffering and protect life may conflict with one another when viewed from the perspective of MAiD. Arguments in favour of including mental illness as a sole qualifier for MAiD include the respect for the autonomy of the individual, and the equivalence of mental illness with physical illness. Arguments against, include the view that the protection of life is paramount, and the “slippery slope” of ever more permissive practices that fail to protect the vulnerable in society. Given the ethical and other practical concerns, there is a need for psychiatric bodies internationally to provide guidance on this issue.